Odonata community in transition areas between Cerrado and Atlantic Forest biomes in south-central Minas Gerais, Brazil - de Gouvêa, Taiguara Pereira (2023)
Faunal inventories are essential for biota management and conservation, especially in areas with potential for the creation of conservation units. Inventories of insect taxa such as dragonflies and damselflies (Odonata), which perform several environmental services in aquatic and terrestrial ecosystems, are of great importance. In view of the above, this study aimed to update and expand the list of Odonata species in the Barroso region, Minas Gerais State, Brazil. This study was carried out in three areas of forest fragments in Atlantic Forest and Cerrado biomes in October 2020, December 2020, January 2021, and March 2021. The sampling effort was 8 hours per day during 20 days, totaling 140 sampling hours. A total of 43 Odonata species were recorded, which increased the richness of the study area from 57 to 76 species. The studied areas harbor rare and endangered species. However, since the last sampling in 2009, there has been a significant reduction in diversity in the Atlantic Forest fragment. In view of the changes that forest fragments are undergoing, we underscore the need to create a conservation unit, especially in Baú Forest.